Implementing Sustainable Procurement Practices in International Hotel - Artini, Ni Komang Maena; Rukmiyati, Ni Made Sri; Yusmarisa, Ni Luh Riska (Indonesian Journal of Banking and Financial Technology, 2024)
This research investigates integrating sustainable procurement practices within international hotel chains, particularly examining their effects on food safety, encountered challenges, stakeholder involvement, and eco-friendly initiatives. It analyzes the impact of sustainable procurement on food quality and safety, highlighting measures undertaken to ensure these standards. The study addresses challenges like balancing quality, cost, and sustainability in food procurement and evaluates hotels' eco-friendly strategies, such as using locally sourced products and effective environmental management. Employing a holistic approach through multiple case studies, the research emphasizes the nexus between food safety and sustainable procurement, offering practical insights for the hospitality industry. The primary principle across international hotel chains is to consider environmental impacts comprehensively in procurement processes, serving as a foundational guideline.